Cardiac monitoring during trastuzumab therapy in metastatic breast cancer: early incidence of cardiac dysfunction - Perone, Francesco; Zamora Auñon, Pilar; Rodríguez, Laura; Vinal, David; Caro-Codon, Juan; Pertejo, Ana; Martínez Marín, Virginia; Espinosa, Enrique; López-Fernández, Teresa (Monaldi Archives for Chest Disease, 2022)
Trastuzumab therapy has dramatically changed breast cancer prognosis. Consensus documents recommend a close monitoring during therapy, not always feasible, especially in metastatic breast cancer. The purpose of this study is to describe trastuzumab cardiotoxicity in metastatic breast cancer patients to understand how to improve cardiovascular monitoring. We retrospectively studied metastatic breast cancer patients scheduled for trastuzumab therapy (2001-2018). All patients underwent a baseline evaluation and monitoring during therapy. Cardiotoxicity was defined as symptomatic heart failure or asymptomatic decrease in left ventricular ejection fraction > 10% from baseline and < 53%. Ninety-two women were included, mean age 61 years (±14.43), median follow-up 42.5 months (IQR 26-74). Fourteen percent developed cardiotoxicity: two heart failure with preserved left ventricular ejection fraction, three heart failure with reduced left ventricular ejection fraction, and eight asymptomatic decreased in left ventricular ejection fraction. Eighty-one percent of cardiac dysfunction cases occurred within the first 4 years and on median of 31 months from trastuzumab initiation. Thus, in metastatic breast cancer patients, trastuzumab-mediated cardiotoxicity occurred more frequently during the first 4 years. These data should be considered to optimize follow-up protocols.